The Effectiveness of Probiotic Administration as A Novel Therapeutic Target for Hypertension During Pregnancy Induced by Primary and Secondary Factors: A Systematic Literature Review of Preclinical Studies - Budi Budi; Nur Indrawaty Lipoeto; Yanwirasti Yanwirasti; Donel Suheimi (Indonesian Journal of Global Health Research, 2025)
Hypertension during pregnancy, including preeclampsia, remains one of the leading causes of maternal and perinatal morbidity and mortality worldwide. The complex pathogenesis of pregnancy-related hypertension involves endothelial dysfunction, impaired angiogenesis, oxidative stress, and immune dysregulation. Conventional pharmacological therapies continue to face limitations in terms of efficacy and safety for pregnant women. Therefore, there is an urgent need for safer and more effective molecular-based therapeutic alternatives, one of which is the use of probiotics. The aim of this systematic review is to analyse the potential effectiveness of probiotic administration as a novel therapeutic target for pregnancy-induced hypertension driven by primary and secondary factors. This systematic review was conducted following the PRISMA guidelines. A comprehensive literature search was performed across databases including Google Scholar, PubMed, Taylor & Francis, and ScienceDirect, covering publications from 2015 to 2025. Inclusion criteria were applied based on the PICOS framework. A total of 14 preclinical in vivo studies met the inclusion criteria. Probiotics such as Akkermansia muciniphila, Bifidobacterium bifidum, Lactobacillus spp., Limosilactobacillus spp., and Lactiplantibacillus plantarum demonstrated significant effectiveness in reducing systolic and diastolic blood pressure, improving endothelial function, suppressing inflammation, and mitigating oxidative stress. These effects were mediated through mechanisms involving gut microbiota modulation and regulation of the renin-angiotensin system. Probiotics hold promise as a safe and effective alternative therapy for reducing hypertension during pregnancy and may support the development of future non-pharmacological, microbiota-based therapeutic strategies.